M&A and the tax benefits of debt-financing - Uwe Scheuering (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
The deductibility of interest expenses from the corporate tax base creates an incentive for acquiring companies to finance a takeover with debt. In this paper, I investigate the impact of profit taxation on the financing decision in corporate acquisitions for the first time for a sample of different acquirer-countries mainly in Europe. The likelihood to observe a debt-financed acquisition is found to increase in the acquirer's tax rate. In addition, I take into account that the financing decisions of particular acquisitions might not be independent from other investment decisions. Therefore, I analyze the acquirer's capital structure development around the acquisition and find an increase in the statutory tax rate by one %-point to be associated with a stronger increase in the debt ratio by 0.55 %-points during the acquisition period.
urn:nbn:de:bsz:180-madoc-365834
Keywords: G34; H25; H32; 330; M&A; Business Taxation; Capital Structure; Empirical Analysis